2019
DOI: 10.2465/jmps.181115
|View full text |Cite
|
Sign up to set email alerts
|

Geochronology and REE geochemistry of zircon and garnet in pelitic gneisses from the Higo metamorphic terrane, Kyushu, Japan: Constraints on the timing of high–temperature metamorphism

Abstract: The Higo metamorphic terrane in west-central Kyushu, southwest Japan, consists of a sequence of greenschistto granulite-facies metamorphic rocks. This study reports the U-Pb Zrn ages and rare earth elements (REE) characteristics of Zrns and Grts from pelitic gneisses in the Higo metamorphic terrane to constrain its timing of high-temperature metamorphism. Based on the morphology, internal textures, occurrences, Th/U ratios, REE patterns and ages of Zrn, and the heavy REE (HREE) partition coefficient between Zr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 29 publications
1
0
0
Order By: Relevance
“…However, the concordant data are selected using the Tera-Wasserburg concordia diagram where the data points are plotted on the concordia within the error bar, only for the SHRIMP data ( Figure 10e). Replotting these data of the previous studies on the Higo Plutono-metamorphic Complex, the youngest three concordant zircon ages of garnet-cordieritebiotite gneiss sample (43007B) (Bui et al, 2019) from metamorphic zone D are revealed as 175 ±12, 178 ±5, and 178 ±6 Ma (Figure 10b).…”
Section: Zircon U-pb Age Of Sambagawa Metamorphic Rocks North Of "Ssupporting
confidence: 72%
“…However, the concordant data are selected using the Tera-Wasserburg concordia diagram where the data points are plotted on the concordia within the error bar, only for the SHRIMP data ( Figure 10e). Replotting these data of the previous studies on the Higo Plutono-metamorphic Complex, the youngest three concordant zircon ages of garnet-cordieritebiotite gneiss sample (43007B) (Bui et al, 2019) from metamorphic zone D are revealed as 175 ±12, 178 ±5, and 178 ±6 Ma (Figure 10b).…”
Section: Zircon U-pb Age Of Sambagawa Metamorphic Rocks North Of "Ssupporting
confidence: 72%